2003
DOI: 10.1161/01.res.0000050585.07097.d7
|View full text |Cite
|
Sign up to set email alerts
|

A Cardiac Sodium Channel Mutation Cosegregates With a Rare Connexin40 Genotype in Familial Atrial Standstill

Abstract: Abstract-Atrial standstill (AS) is a rare arrhythmia that occasionally appears to be genetically determined. This study investigates the genetic background of this arrhythmogenic disorder in a large family. Forty-four family members were clinically evaluated. One deceased and three living relatives were unambiguously affected by AS. All other relatives appeared unaffected. Candidate gene screening revealed a novel mutation in the cardiac sodium channel gene SCN5A (D1275N) in all three affected living relatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
221
1
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 259 publications
(237 citation statements)
references
References 35 publications
11
221
1
3
Order By: Relevance
“…Biophysical studies of Na channel function have shown that mutations that evoke LQT3 cause excessive Na current (gain-of-function), delaying repolarization and causing early after depolarizations resulting in Torsades de Pointes 13 , whereas Brugada syndrome mutations reduce Na current (loss-of-function), causing premature epicardial repolarization and phase 2 reentry leading to ventricular tachycardia or fibrillation 14 . SCN5A mutations have also been identified in supraventricular arrhythmias such as congenital AV block 15 , sick sinus syndrome (SSS) 12 , and AS 5,6 , but the mechanisms are less well defined as compared with those of ventricular arrhythmias. The present study describes clinical, genetic and biophysical features of the novel SCN5A mutation, L212P, found in a family with congenital progressive AS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Biophysical studies of Na channel function have shown that mutations that evoke LQT3 cause excessive Na current (gain-of-function), delaying repolarization and causing early after depolarizations resulting in Torsades de Pointes 13 , whereas Brugada syndrome mutations reduce Na current (loss-of-function), causing premature epicardial repolarization and phase 2 reentry leading to ventricular tachycardia or fibrillation 14 . SCN5A mutations have also been identified in supraventricular arrhythmias such as congenital AV block 15 , sick sinus syndrome (SSS) 12 , and AS 5,6 , but the mechanisms are less well defined as compared with those of ventricular arrhythmias. The present study describes clinical, genetic and biophysical features of the novel SCN5A mutation, L212P, found in a family with congenital progressive AS.…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified a missense mutation R367H in a transient AS case complicated with Brugada syndrome 5 , and the recombinant channel showed total loss of Na current when expressed heterologously. In contrast, another SCN5A mutation, D1275N, found in a small Dutch kindred with progressive AS, showed relatively benign biophysical abnormalities 6 . Moreover, some mutation carriers in this pedigree exhibit a normal electrocardiogram, and further screening of atria-specific genes has demonstrated that the affected individuals exclusively carry both D1275N mutation and homozygous polymorphisms in the regulatory region of connexin 40 (Cx40), supporting an argument favoring digenic inheritance.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations